Techno-economic analysis of hybrid ACC performance under different meteorological conditions - du Plessis, Jacques; Owen, Michael (Energy (Oxford), 2022)
A hybrid air-cooled condenser (ACC) concept has demonstrated to provide performance benefits over a conventional ACC. Additional to the thermal performance, the cost effectiveness should also be considered to determine the commercial viability, and therefore this study interrogates the techno-economic feasibility of a hybrid ACC at six locations with a ∼238 MW steam turbine representative of a typical CSP or NGCC plant. In this paper the hybrid ACC, is compared to a conventional ACC in terms of annual performance and annualized cost. The annualized cost of the hybrid ACC relative to the conventional ACC is expressed as a cost ratio φₐ, and consideration is given to a range of water and hybrid unit capital costs. The hybrid ACC is 12% more capital intensive per street, but the hybrid ACC requires about ⅓ fewer units and consume 30% less auxiliary power. This results in a higher annual net power generation while the annual specific water consumption ranged between 0.31 kL/MWh and 0.69 kL/MWh across the six sites. At drier sites the hybrid ACC can be oversized to reduce the water consumption with 50%. The cost evaluation demonstrates that the hybrid ACC is best suited to locations with low to moderate humidity. •A hybrid air-cooled condenser (ACC) provides improved performance.•The hybrid ACC is more capital intensive, but require fewer units.•Compared to a conventional ACC the hybrid ACC is economically viable.•The hybrid ACC is best suited for low to moderate humidity locations.•At drier sites the system can be oversized to reduce the water consumption.